2020
DOI: 10.1371/journal.pone.0240423
|View full text |Cite
|
Sign up to set email alerts
|

Beyond maternal education: Socio-economic inequalities in children’s diet in the ABCD cohort

Abstract: We examined whether the role of maternal education in children's unhealthy snacking diet is moderated by other socioeconomic indicators. Methods Participants were selected from the Amsterdam Born Children and their Development cohort, a large ongoing community-based birth cohort. Validated Food Frequency Questionnaires (FFQ) (n = 2782) were filled in by mothers of children aged 5.7±0.5yrs. Based on these FFQs, a snacking dietary pattern was derived using Principal Component Analysis. Socioeconomic indicators w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Due to social disparities in dietary intake and diet quality [ 14 ], nutritional benefits of family meal participation may differ according to parental education and family socioeconomic position. In a meta-analysis of studies addressing family meals and nutritional health in children, Dallacker et al [ 10 ] found that socioeconomic position slightly moderated the association between frequency of family meals and BMI, but not associations with healthy diet, unhealthy diet, and overall diet quality.…”
Section: Introductionmentioning
confidence: 99%
“…Due to social disparities in dietary intake and diet quality [ 14 ], nutritional benefits of family meal participation may differ according to parental education and family socioeconomic position. In a meta-analysis of studies addressing family meals and nutritional health in children, Dallacker et al [ 10 ] found that socioeconomic position slightly moderated the association between frequency of family meals and BMI, but not associations with healthy diet, unhealthy diet, and overall diet quality.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that maternal educational level, measured as a proxy of the child’s socioeconomic status, is related to the child’s diet quality, physical activity, and screen time [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Cross-sectional data indicates that children whose mothers have a low educational level are at higher risk of reporting an unhealthy diet, a low level of physical activity, and high level of screen time [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional data aid in hypothesis generation and establish an association, but prospective studies are needed to determine whether these associations may change over time. However, prospective data is somewhat limited [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Therefore, the aim of the present study was to analyze the association of baseline maternal educational level with child’s physical activity, screen time and dietary habits at follow-up, in a Spanish cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the age of the children, the increased household size was also significantly associated with increased dietary quality score. However, a few studies have revealed that parents' education level and household were significantly associated with the diet quality of the children instead of household size (Rashid et al, 2020;van der Velde et al, 2019).…”
Section: Discussionmentioning
confidence: 99%